Molecular Analysis of Neutrophil Differentiation from Human Induced Pluripotent Stem Cells Delineates the Kinetics of Key Regulators of Hematopoiesis. (29th February 2016) - Sweeney, Colin L.; Teng, Ruifeng; Wang, Hongmei; Merling, Randall K.; Lee, Janet; Choi, Uimook; Koontz, Sherry; Wright, Daniel G.; Malech, Harry L.
Abstract: In vitro generation of mature neutrophils from human induced pluripotent stem cells (iPSCs) requires hematopoietic progenitor development followed by myeloid differentiation. The purpose of our studies was to extensively characterize this process, focusing on the critical window of development between hemogenic endothelium, hematopoietic stem/progenitor cells (HSPCs), and myeloid commitment, to identify associated regulators and markers that might enable the stem cell field to improve the efficiency and efficacy of iPSC hematopoiesis. We utilized a four-stage differentiation protocol involving: embryoid body (EB) formation (stage-1); EB culture with hematopoietic cytokines (stage-2); HSPC expansion (stage-3); and neutrophil maturation (stage-4). CD34 + CD45 − putative hemogenic endothelial cells were observed in stage-3 cultures, and expressed VEGFR-2/Flk-1/KDR and VE-cadherin endothelial markers, GATA-2, AML1/RUNX1, and SCL/TAL1 transcription factors, and endothelial/HSPC-associated microRNAs miR-24, miR-125a-3p, miR-126/126*, and miR-155. Upon further culture, CD34 + CD45 − cells generated CD34 + CD45 + HSPCs that produced hematopoietic CFUs. Mid-stage-3 CD34 + CD45 + HSPCs exhibited increased expression of GATA-2, AML1/RUNX1, SCL/TAL1, C/EBPα, and PU.1 transcription factors, but exhibited decreased expression of HSPC-associated microRNAs, and failed to engraft in immune-deficient mice. Mid-stage-3 CD34 − CD45 + cells maintained PU.1 expression and exhibited increased expression of hematopoiesis-associated miR-142-3p/5p and a trend towards increased miR-223 expression, indicating myeloid commitment. By late Stage-4, increased CD15, CD16b, and C/EBPε expression were observed, with 25%-65% of cells exhibiting morphology and functions of mature neutrophils. These studies demonstrate that hematopoiesis and neutrophil differentiation from human iPSCs recapitulates many features of embryonic hematopoiesis and neutrophil production in marrow, but reveals unexpected molecular signatures that may serve as a guide for enhancing iPSC hematopoiesis.